2013
DOI: 10.3233/ch-121651
|View full text |Cite
|
Sign up to set email alerts
|

Contrast-enhanced ultrasound versus conventional ultrasound in the diagnosis of polypoid lesion of gallbladder: A multi-center study of dynamic microvascularization

Abstract: OBJECTIVE: To assess the value of contrast-enhanced ultrasound (CEUS) in the diagnosis of polypoid lesions of gallbladder (PLGs). METHODS: CEUS was performed to 116 patients (mean age, 49.6 years; range, 21-80 years) with PLGs from 8 university hospitals. 9 cases of biliary sludge were proven by surgery and the remaining 107 cases were confirmed by histopathological examination. The confidence level, diagnostic performance, inter-observer agreement of two independent readers with different experience was asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 33 publications
0
25
0
Order By: Relevance
“…Further identification excluded 94 articles that were not of interest for this meta-analysis and 44 papers that failed to provide sufficient or related data for the calculation of diagnostic accuracy. Finally, 21 articles satisfying the inclusion criteria were included and analyzed [2,7,8,[17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34]. The demonstration of study search flow can be seen in Fig.…”
Section: Study Identificationmentioning
confidence: 99%
“…Further identification excluded 94 articles that were not of interest for this meta-analysis and 44 papers that failed to provide sufficient or related data for the calculation of diagnostic accuracy. Finally, 21 articles satisfying the inclusion criteria were included and analyzed [2,7,8,[17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34]. The demonstration of study search flow can be seen in Fig.…”
Section: Study Identificationmentioning
confidence: 99%
“…In recent years, new techniques such as contrastenhanced ultrasound have been used to depict intralesional vascularity of PLGs. [6][7][8] Sadamoto et al 9 have also constructed Diagnosis of gallbladder polyps X-S Liu et al…”
Section: Discussionmentioning
confidence: 99%
“…The downside to this study however, is that it did not compare contrast-enhanced ultrasonography with CUS[ 28 ]. Zheng et al[ 29 ] did compare the two modalities in a study of 116 patients with gallbladder polyps, and found that CEUS was useful for improving diagnostic accuracy in polyps greater than 10 mm, but not less than 10 mm in size.…”
Section: The Role Of Different Imaging Modalities In Gallbladder Polymentioning
confidence: 99%